Postprandial triglyceride levels affecting postprandial thyroid stimulating hormone levels may be responsible for the increased postprandial thyroid stimulating hormone levels in people with reduced lipid tolerance - Tian, Peipei; Zeng, Shaojing; Hou, Yilin; Liu, Dandan; Lu, Yamin; Song, Guangyao (Frontiers in Endocrinology, 2025)
ObjectiveIn this study, we aimed to explore the relationship between postprandial triglyceride (TG) and postprandial thyroid stimulating hormone (TSH) levels and compare the postprandial TSH levels in participants with normal lipid tolerance and reduced lipid tolerance.MethodsA total of 81 eligible participants were enrolled and given a high-fat meal of 1500 kcal, and blood samples were collected at 2, 4, 6, and 8 hours. Fasting blood glucose, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and fasting and postprandial TG, triiodothyronine (T3), tetraiodothyronine (T4), and TSH levels were tested. Based on the postprandial serum TG level, participants were divided into the normal lipid tolerance group (NFT) and the decreased lipid tolerance group (IFT).ResultsPostprandial TG levels increased in both the NFT and IFT groups and then decreased over time. A higher and delayed peak of postprandial TG was observed in the IFT group, and there were statistically significant differences in TG levels at each time point in both groups. The area under the curve (TGAUC) was an independent influencing factor for the area under the curve (TSHAUC) of TSH. Postprandial TSH levels in both groups reached a trough at 2 h and peaked at 6 h, with a higher peak in the IFT group. Except for 2 h, TSH levels were significantly different at all other time points. There was no statistically significant difference in T3 or T4 levels between the two groups, with opposite trends for TSH.ConclusionAfter a high-fat meal is consumed, the postprandial TSH level is influenced by the postprandial TG level, which may be the reason for the decreased thyroid function in the population with reduced lipid tolerance.Clinical Trial Registrationhttp://www.chictr.org.cn/index.aspx, identifier ChiCTR1800019514.